Para cuidar da salvação das Almas nos dois lados do Atlântico: a confraria de S. Nicolau Tolentino e Almas de Braga (séculos XVII- XVIII) - Maria Marta Lobo de Araújo (Nuevo mundo - Mundos Nuevos, 2021)
In this work we will try to analyze the performance of the confraternities of the Souls of Purgatory in the city of Braga, making known their role as caretakers of the Souls who suffered in the fire of Purgatory. The action of these institutions grew with Trento, reaching great popularity among the believers. The fear of Purgatory, the place from which Souls could be redeemed, led everyone who could enroll in these institutions to enjoy the benefits they sponsored. It was mainly through prayer, the celebration of masses, but also charitable actions, that the living interceded for the dead. The 14 confraternities of the Souls of Braga marked a notable presence in the world of the dead, promoting the celebration of many masses in order to rescue the Souls of all, because, contrary to the others, they took care of the health of all suffering Souls. Thus, we will study the statutes, the books of minutes and the income and expense books, giving particular attention to the confraternity of S. Nicolau Tolentino of the Souls of the church of the Pópulo convent in the city of Braga in the connection of one of its members with Brazil.